Formation of Disciplinary Character Based on School Culture for Students' Work Readiness - Olivia, Bintan; Ansor, Sharifah Radhiana; Sari, Yunita; Setyowati, Arbin Janu; Ratnasari, Intan; Saputra, Nur Mega Aris (Universitas Negeri Malang, 2024)
Character education can be implemented in the world of education through the school culture adopted. Therefore, this study aims to determine the role of school culture in shaping students' disciplinary character as preparation for entering the world of work. This research uses a qualitative approach with a case study type. The data collection technique used the interview method. There are research subjects including the Head of Student Affairs, Guardian Teachers, parents, and students who are determined based on the limitations of the research problem. the results concluded that: (1) SMK PGRI 3 Malang has a school culture as an effort to shape students' disciplinary character through programs, policies, behavior monitoring and evaluation of the achievement of students' disciplinary character building with the aim of preparing students to enter the world of work, (2) the role in shaping disciplinary character is carried out by all school residents and parents, (3) there are supporting factors in the form of teachers and employees becoming role models, support from guardian teachers who collaborate with parents, clear rules, extracurricular activities and available facilities and (4) there are inhibiting factors, namely student awareness, the environment outside the school and social media. Keywords: discipline character; discipline school; work readiness; student SMK